Export Promotion Rationales and Impacts – A Review - Eero Aalto; Robin Gustafsson (The Research Institute of the Finnish Economy (ETLA), 2020)
We review the extant research on the government export promotion policy interventions, concentrating on export promotion agencies (EPA). Based on the research literature, the review synthesizes export promotion policy intervention rationale and economic justifications for the intervention, impact evaluations of the export promotion interventions, and current forms of export promotion. We identify two types of information related market failures, information spillovers and information asymmetry, justifying public intervention and use of public funds to support firm exporting. Furthermore, four distinct economic and non-economic policy outcome objectives can be identified, accrued in the firm, industry or macro-economic level from increased exporting. Export promotion policy intervention as such impacts both export performance of firms, as well as industry and macro-economic performance of a country. However, export promotion impact studies indicate heterogenous effects on countries, firms, export barrier types, markets and products. With regards to policy interventions, it is especially SME firms who lack key competences to operate in the foreign markets. EPA services can help SMEs to overcome the external and internal barriers to internationalization by providing information, training, and other types of support as external resources. Public policy interventions are as such a means to share risks and to offer motivational stimuli for the SME executives to seek growth in the foreign markets.
Keywords: D83; F20; L15; N70; 330; Export promotion; Export promotion agencies; Impact evaluation; Policy rationales